Microbiological Findings in Prepubertal Girls with Vulvovaginitis - Šikanić-Dugić, Nives; Pustišek, Nives; Hiršl-Hećej, Vlasta; Lukić-Grlić, Amarela (2009)
Summary: The aim of the study was to define the most common causes, symptoms and clinical features of vulvovaginitis in prepubertal girls, and to evaluate treatment success depending on the causative agent involved.
Bibliografija: 21 jed
Keywords: Vulvovaginitis -- Djevojčice